2022
DOI: 10.17159/2411-9717/1059/2022
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of SiC reinforcement ratio in iron-based composite materials on corrosion properties

Abstract: The corrosion properties of iron-based composite materials containing graphite and silicon carbide (SiC) reinforcement were investigated. The effects of silicon carbide reinforcement were investigated by adding 0.5% graphite and 1%, 2%, and 4% SiC. A powder metallurgy method was used to produce the composite samples. Iron, graphite, and silicon carbide powders were blended for one hour with a three-axis mixer and then unidirectionally pressed under a pressure of 750 MPa. After pressing, the composite materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Another study investigated the effect of Nb and Al addition to micro-alloy steels produced with powder metallurgy on microstructure and mechanical properties and observed that the mechanical properties improved with Nb and Al addition. In the study, SEM, EDS, and XRD analyses were applied, and NbC was associated with precipitates, which occur with precisions, increased strength as well as grain size [35][36][37][38][39][40][41][42][43][49][50][51][52][53][54]. When Figures 7 and 8 are examined, it is observed that the production of single and layered composites up to 40% Al 2 O 3 with 316L stainless steel matrix is carried out successfully.…”
Section: Yield Stress Uts Elongationmentioning
confidence: 99%
“…Another study investigated the effect of Nb and Al addition to micro-alloy steels produced with powder metallurgy on microstructure and mechanical properties and observed that the mechanical properties improved with Nb and Al addition. In the study, SEM, EDS, and XRD analyses were applied, and NbC was associated with precipitates, which occur with precisions, increased strength as well as grain size [35][36][37][38][39][40][41][42][43][49][50][51][52][53][54]. When Figures 7 and 8 are examined, it is observed that the production of single and layered composites up to 40% Al 2 O 3 with 316L stainless steel matrix is carried out successfully.…”
Section: Yield Stress Uts Elongationmentioning
confidence: 99%
“…The powder metallurgy approach involves gas atomization, water atomization, mechanical alloying, chemical electrolysis, and other techniques. It is a self-contained production technique that includes secondary processes such as mixing metal content lithose produced by powder production methods in specific proportions, filling it into a mold with the desired shape and pressing it, sintering process and, if necessary, hole drilling, surface hardening, secondary pressing [17][18][19][20][21][22][23][24][25]. Nickel acts as an austenite stabilizer.…”
Section: Introductionmentioning
confidence: 99%